Towards a Universal Clinical Genomics Database: The 2012 International Standards for Cytogenomic Arrays (ISCA) Consortium Meeting - Riggs, Erin Rooney (2013)
The 2012 International Standards for Cytogenomic Arrays (ISCA) Consortium Meeting, “Towards a Universal Clinical Genomic Database,” was held in Bethesda, MD, 21–22 May 2012 and was attended by over 200 individuals from around the world representing clinical genetic testing laboratories, clinicians, academia, industry, research, and regulatory agencies. The scientific program centered on expanding the current focus of the ISCA Consortium to include the collection and curation of both structural and sequence-level variation into a unified clinical genomics database, available to the public through resources such as the National Center for Biotechnology Information (NCBI)’s ClinVar database. Here, we provide an overview of the conference, with summaries of the topics presented for discussion by over 25 different speakers. Presentations are available online at www.iscaconsortium.org.